Identification of temperature tolerant sunflower (Helianthus annuus L.) inbreds: Identification of temperature tolerant sunflower (Helianthus annuus L.) inbreds - V APARNA; LAKSHMI PRAYAGA; ARTI GUHE; P LAKSHMAMMA (Journal of Oilseeds Research, 2020)
Forty seven lines including CMS and R lines with 4 hybrids DRSH-1, KBSH-44, CO-2 and CSFH-12205 were evaluated for temperature tolerance under field conditions by taking two sowing dates one normal and one delayed sowing to expose the crop to high temperatures. Six lines were found tolerant with <15% yield reduction for a mean temperature rise of 6.1°C during the crop growth period.